Enterprise and Organizational Modeling and Simulation 9th International Workshop, EOMAS 2013, Held at CAiSE 2013, Valencia, Spain, June 17, 2013, Selected Papers - Barjis, Joseph; Gupta, Ashish; Meshkat, Amir.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book constitutes the proceedings of the 9th International Workshop on Enterprise and Organizational Modeling and Simulation, EOMAS 2013, held in conjunction with CAiSE 2013 in Valencia, Spain, in June 2013. Tools and methods for modeling and simulation are widely used in enterprise engineering, organizational studies, and business process management. In monitoring and evaluating business processes and the interactions of actors in a realistic environment, modeling and simulation have proven to be both powerful, efficient, and economic, especially if complemented by animation and gaming elements. The ten contributions in this volume were carefully reviewed and selected from 22 submissions. They explore the above topics, address the underlying challenges, find and improve solutions, and show the application of modeling and simulation in the domains of enterprises, their organizations and underlying business processes.
A Literature Review on Business Process Management, Business Process Reengineering and Business Process Innovation -- Issues about Inter-organizational Process Flow Adjustment in Business Process Modeling -- An Approach for a Mutual Integration of the Web of Things with Business Processes -- Translating DEMO Models into Petri Net -- Role of OBA Approach in Object-Oriented Process Modelling and Simulation -- Instance-Level Modelling and Simulation Revisited -- Cloud ERP Query Flow Control Simulation with Quality Restrictions and Profit Gaining Criteria -- Developing a Multi-facet Abstractions Framework for Designing a New Class of Traceability Applications -- Multi-level Architecture on Web Services Based Policy Domain Use Cases Simulator -- Component-Based Design for Multi-tenant Multi-target Support in the Cloud.
Keywords: Economics; Computer simulation; Information systems; Management information systems; Economics/Management Science; Business Information Systems; Computer Appl. in Administrative Data Processing; Information Systems Applications (incl. Internet).; Simulation and Modeling